2021
DOI: 10.1073/pnas.2115367118
|View full text |Cite
|
Sign up to set email alerts
|

Flexible cyclic-olefin with enhanced dipolar relaxation for harsh condition electrification

Abstract: Flexible large bandgap dielectric materials exhibiting ultra-fast charging-discharging rates are key components for electrification under extremely high electric fields. A polyoxafluoronorbornene (m-POFNB) with fused five-membered rings separated by alkenes and flexible single bonds as the backbone, rather than conjugated aromatic structure typically for conventional high-temperature polymers, is designed to achieve simultaneously high thermal stability and large bandgap. In addition, an asymmetrically fluorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…In addition, further increased ε r , T g and band gap can be obtained by changing the CF 3 substitution position on the benzene ring. [ 195,196 ]…”
Section: Thermal Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, further increased ε r , T g and band gap can be obtained by changing the CF 3 substitution position on the benzene ring. [ 195,196 ]…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…In addition, further increased ε r , T g and band gap can be obtained by changing the CF 3 substitution position on the benzene ring. [195,196] Crosslinking is an effective approach to form a compact chain structure, and the tight network can be kept under high thermal stress and high electric field. Therefore, high thermal stability and high U d of crosslinked polymers have been achieved.…”
Section: Enhancing Thermal Stability Of Polymersmentioning
confidence: 99%
“…5 More importantly, the high breakdown strength and special capacitor failure mode of polymeric dielectrics are beneficial for enhancing the working reliability of capacitors under high electric fields. 6 Meanwhile, the energy density of polymer dielectrics is an order of magnitude lower than that of supercapacitors and electrochemical batteries, which limits their applications in many fields. The biaxially oriented polypropylene (BOPP) film is a state-of-the-art dielectric film for commercial capacitors, whose maximum discharged energy density is about 4 J cm −3 , which is far from requested.…”
Section: Introductionmentioning
confidence: 99%
“…Cao's group synthesized a series of dipolar relaxation enhanced cyclic olefins with a U e of ∼9 J cm −3 , an E b of ∼750 MV m −1 and rather high T g (∼178 °C). 6 Unfortunately, they suffer from similar problems of high dielectric loss due to the polarization relaxation of polar groups under a high electric field, especially at elevated temperature, which leads to significantly reduced discharging efficiency. Besides, glassy polymers are usually rigid at room temperature, which makes them hard to fabricate into free standing thin films with required mechanical strength for the subsequent capacitor processing procedure like BOPP.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric position of –CF 3 in m -POFNB leads to enhanced dipolar polarization which results in increase in dielectric constant. 33 Although, in the case of p -POFNB, free rotation of the pedant group is available but the symmetric position of –CF 3 results in a lower dipole moment in total, leading to lower dielectric constant relative to m -POFNB and o -POFNB. 34 It has been demonstrated that the electronic part of the dielectric constant reveals an inverse relationship with the bandgap.…”
mentioning
confidence: 99%